2018
DOI: 10.1128/aac.00241-18
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Significance of Aspergillus fumigatus cyp51A Polymorphisms

Abstract: Triazole antifungal compounds are the first treatment choice for invasive aspergillosis. However, in the last decade the rate of azole resistance among strains has increased notoriously. The main resistance mechanisms are well defined and mostly related to point mutations of the azole target, 14-α sterol demethylase (), with or without tandem repeat integrations in the promoter. Furthermore, different combinations of five Cyp51A mutations (F46Y, M172V, N248T, D255E, and E427K) have been reported worldwide in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 68 publications
6
58
1
Order By: Relevance
“…Thus, despite a concentration of 4.3 mg/L (within the recommended trough range), potential subtherapeutic levels during the 200 mg 2×/d dosing scheme cannot be ruled out. The F46Y/M172V/E427K substitutions in Cyp51A, found in both susceptible and resistant isolates, have been suggested to play no role or only a minor role in reduced azole susceptibilities ( 12 , 13 ). TRs in the promoter region of cyp51A have previously been linked to increased cyp51A gene expression and MICs because of duplicated srbA transcription factor binding motifs (SRE1 and SRE2) leading to increased expression of cyp51A ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, despite a concentration of 4.3 mg/L (within the recommended trough range), potential subtherapeutic levels during the 200 mg 2×/d dosing scheme cannot be ruled out. The F46Y/M172V/E427K substitutions in Cyp51A, found in both susceptible and resistant isolates, have been suggested to play no role or only a minor role in reduced azole susceptibilities ( 12 , 13 ). TRs in the promoter region of cyp51A have previously been linked to increased cyp51A gene expression and MICs because of duplicated srbA transcription factor binding motifs (SRE1 and SRE2) leading to increased expression of cyp51A ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity could potentially lead to confusion, so care must be taken in drawing conclusions on different aspects from a single genetic background [ 15 ]. A recent study carried out in our laboratory [ 19 ] showed that the Af293 reference genome belonged to a specific lineage of A. fumigatus strains which harbors five polymorphisms (F46Y, M172V, N248T, D255E, E427K) in cyp51A gene which codes for the azole target. Based on these phylogenetic studies from whole genome sequencing, the other classic reference genome, the A1163 strain, belonged to a different and distant phylogenetic lineage, which implies that both genomes are significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33,[45][46][47][48][49][50][51], Aspergillus spp. [13,29,35,[52][53][54][55][56][57][58][59][60][61], Mucorales [62][63][64], Madurella mycetomatis [65][66][67], and other fungal agents [68][69][70]. The contribution of G. mellonella to the evaluation of antifungal drugs will be detailed in the following paragraphs.…”
Section: Evaluation Of Antifungal Efficacy In Galleria Mellonellamentioning
confidence: 99%
“…The treatment of G. mellonella infected with Aspergillus spp. has been evaluated in several studies (Table 4) in order to assess intrinsic resistance in specific species [55,56,83], acquired azole resistance in A. fumigatus [53,54], combinations [35,59], and efficacy of non-antifungal drugs [29,57,58,60,61]. A. fumigatus VRZ (10) AMB (3) sertraline (3,10)…”
Section: Aspergillus Sppmentioning
confidence: 99%
See 1 more Smart Citation